Contractual Agreements in Banking Operations Without Usury According to the Theory of the Liability of Money - Sayyid Mustafa Mohaqqiq Damad; Sayyid Mojtaba Madani Bajestani (آموزه‌‌های فقه مدني, 2023)
A contract in the conventional banking is signed between the bank and the customer in the form of a loan contract and a certain interest is paid in accordance with the contractual agreement. The use of partnership and non-partnership contracts according to the religious prohibition of receiving profits in the contract of debt in banking operations without usury to receive profits has been studied by many experts and Law for Usury (law on banking operations without usury) has been prepared, approved and implemented accordingly. However, the use of these contracts has caused the complexity, cost and formalization of the contracts and led them to be corporatism. Providing a solution to solve this problem by using the current opinions about the money liability theory (monetary theory) is the purpose of this article. In addition to the devaluation of money, loss of benefits and delayed payment fine (late payment fine) have also been studied in the light of this theory and due to the nature of money in the modern economy in the form of contractual agreements and condition as an integral part of contract (proviso) in the contract. The use of contractual agreements according to the opinions presented about the theory of money liability in banking contracts can be helpful in resolving this problem.